Antihyperglycemic Activity Test of Ethanol Extract, Methanol and n-Hexane Fraction of Taro Leaves (Colocasia esculenta (L) Schott) - Rachma Nurhayati; Nadia Pramasari; Rosa Hesturini (Jurnal Ilmiah Sains, 2023)
Taro leaf (Colocasia esculenta (L) Schott) is a plant from the Araceae family that has antihyperglycemic activity because it contains secondary metabolites such as flavonoids, tannins, saponins, polyphenols and alkaloids. This study was aimed to determine the antihyperglycemic activity of ethanol extract, methanol fraction and n-hexane fraction of taro leaves given to male white rats after streptozotocin and alloxan were induced. The experimental research method used 55 male white rats with 6 treatments. Group 1 normal, group 2 negative control CMC-Na, group 3 positive control metformin 500 mg, group 4 ethanol extract at a dose of 200 mg/Kgbb (streptozotocin induction), group 5 methanol fraction at a dose of 38, 1 mg/KgBW (streptozotocin induction), group 6 n-hexane fraction at a dose of 9,2 mg/KgBW (streptozotocin induction), group 7 ethanol extract at a dose of 200 mg/Kgbb (aloxan induction), group 8 methanol fraction at a dose of 38, 1 mg/KgBW (aloxan induction) and group 9 n-hexane fraction at a dose of 9,2 mg/KgBW (aloxan induction). Glucose levels were checked using an Easy Touch glucometer. The results showed that statistically the ethanol extract of taro leaves at a dose of 200 mg/KgBW was the most effective in lowering blood glucose in male white rats. Keywords: Antihyperglycemia; extract; fraction; taro leaves